"Why would anybody do this?": Older Adults' Understanding of and Experiences with Crowd Work - Brewer, Robin; Morris, Meredith Ringel; Piper, Anne Marie (Proceedings of CHI 2016, 2016)
Diversifying participation in crowd work can benefit the worker and requester. Increasing numbers of older adults are online, but little is known about their awareness of or how they engage in mainstream crowd work. Through an online survey with 505 seniors, we found that most have never heard of crowd work but would be motivated to complete tasks by earning money or working on interesting or stimulating tasks. We follow up results from the survey with interviews and observations of 14 older adults completing crowd work tasks. While our survey data suggests that financial incentives are encouraging, in-depth interviews reveal that a combination of personal and social incentives may be stronger drivers of participation, but only if older adults can overcome accessibility issues and understand the purpose of crowd work. This paper contributes insights into how crowdsourcing sites could better engage seniors and other users.